Weedpatch Committee - Lev Grigorevich Brodaty:::Creator::::::::::::
Glava Dvadtsat Tretya' (Chapter 22). Committee members who come to speak with Ma. Pen and ink lithograph.Lev Grigorevich Brodaty was born in Warsaw in 1889. A graphic artist, poster artist and illustrator, he created these for a Russian translation (possibly the first) of The Grapes of Wrath. He died in Moscow in 1954.